Anatomical Classification and Posttreatment Remodeling Characteristics to Guide Management and Follow-Up of Neonates and Infants With Coronary Artery Fistula: A Multicenter Study From the Coronary Artery Fistula Registry. (22nd December 2021) - Gowda, Srinath T.; Latson, Larry; Sivakumar, Kothandam; Hiremath, Gurumurthy; Crystal, Matthew; Law, Mark; Shahanavaz, Shabana; Asnes, Jeremy; Veeram Reddy, Surendranath; Kobayashi, Daisuke; Alwi, Mazeni; Ichida, Fukiko; et al.
Abstract : Background: Coronary artery fistulas (CAFs) presenting in infancy are rare, and data regarding postclosure sequelae and follow-up are limited. Methods: A retrospective review of all the neonates and infants (<1 year) was conducted from the CAF registry for CAF treatment. The CAF type (proximal or distal), size, treatment method, and follow-up angiography were reviewed to assess outcomes and coronary remodeling. Results: Forty-eight patients were included from 20 centers. Of these, 30 were proximal and 18 had distal CAF; 39 were large, 7 medium, and 2 had small CAF. The median age and weight was 0.16 years (0.01–1) and 4.2 kg (1.7–10.6). Heart failure was noted in 28 of 48 (58%) patients. Transcatheter closure was performed in 24, surgical closure in 18, and 6 were observed medically. Procedural success was 92% and 94 % for transcatheter closure and surgical closure, respectively. Follow-up data were obtained in 34 of 48 (70%) at a median of 2.9 (0.1–18) years. Angiography to assess remodeling was available in 20 of 48 (41%). I. Optimal remodeling (n=10, 7 proximal and 3 distal CAF). II. Suboptimal remodeling (n=7) included (A) symptomatic coronary thrombosis (n=2, distal CAF), (B) asymptomatic coronary thrombosis (n=3, 1 proximal and 2 distal CAF), and (C) partial thrombosis with residual cul-de-sac (n=1, proximal CAF) and vessel irregularity with stenosis (n=1, distal CAF). Finally, (III) persistent coronary artery dilation (n=4). Antiplatelets and anticoagulation were used in 31 and 7 patients post-closure, respectively. Overall, 7 of 10 (70%) with proximal CAF had optimal remodeling, but 5 of 11 (45%) with distal CAF had suboptimal remodeling. Only 1 of 7 patients with suboptimal remodeling were on anticoagulation. Conclusions: Neonates/infants with hemodynamically significant CAF can be treated by transcatheter or surgical closure with excellent procedural success. Patients with distal CAF are at higher risk for suboptimal remodeling. Postclosure anticoagulation and follow-up coronary anatomic evaluation are warranted.